2006
DOI: 10.1074/jbc.m606736200
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β-(1-42) Increases Ryanodine Receptor-3 Expression and Function in Neurons of TgCRND8 Mice

Abstract: Disruption of intracellular calcium homeostasis precedes the neurodegeneration that occurs in Alzheimer disease (AD).In experiments performed in nominal extracellular calcium, neurons from Tg mice had significant increases in intracellular calcium following ryanodine or glutamate treatment compared with littermate controls, which was abolished by treatment with small interfering RNA directed to RyR-3, indicating that the higher levels of calcium originated from RyR-3-regulated stores. Taken together, these obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
91
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 44 publications
(42 reference statements)
5
91
0
1
Order By: Relevance
“…[51][52][53] An increased expression of the ryanodine receptor (RYR), particularly the RYR3 isoform, 53 is one cause for this hypersensitivity of the internal release mechanism. 52,[54][55][56] The increase in RYR expression results in a greater sensitivity to Ca 2+ elevations during normal synaptic transmission.…”
Section: Bipolar Disordermentioning
confidence: 99%
“…[51][52][53] An increased expression of the ryanodine receptor (RYR), particularly the RYR3 isoform, 53 is one cause for this hypersensitivity of the internal release mechanism. 52,[54][55][56] The increase in RYR expression results in a greater sensitivity to Ca 2+ elevations during normal synaptic transmission.…”
Section: Bipolar Disordermentioning
confidence: 99%
“…Studies in brain slice preparations have also revealed increased RyRevoked Ca 2ϩ responses across specific neuronal compartments, including the soma and perinuclear regions, and particularly high release in dendrites and spine heads (Stutzmann et al, 2006;Goussakov et al, 2010). In asymptomatic young mice, this was associated with an increase in the RyR2 isoform (Chakroborty et al, 2009), whereas increased RyR3 expression has been observed at later disease stages concurrent with A␤ 1-42 expression (Supnet et al, 2006). Although mutant PS1-expressing mice seem to be cognitively and neurophysiologically normal at this younger, presymptomatic age (Oddo et al, 2003), upon manipulation of the RyR-sensitive stores, it is apparent that these neurons are using a markedly different Ca 2ϩ signaling system to support neurotransmission and plasticity (Chakroborty et al, 2009).…”
Section: E Alzheimer Diseasementioning
confidence: 99%
“…Concomitant with the impairment in leak channel function, the increase in RyR expression is thought to be a compensatory and neuroprotective response to assume the leak channel role and normalize ER store levels . Other neuroprotective roles of the RyR3 isoform have also been proposed at later disease stages, such that increased RyR3 expression is observed upon A␤ 42 exposure, whereas knockdown of RyR3 increases amyloid pathologic condition (Supnet et al, 2006. Likewise, long-term exposure to RyR blockers increases amyloid pathologic condition and cytotoxicity .…”
Section: E Alzheimer Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, expression and functional activity of CD38 in astrocytes and/or neurons, and ectocellular action of cADPR and NAADP + on astrocytes resulting in Ca 2+ signaling (Heidemann et al, 2005;Pawlikowska et al, 1996) would have physiological and pathophysiological meaning as a mechanism of Ca 2+ signaling involved in neuron-astroglia cell interactions. Alterations in ryanodine receptor binding and function are very early events in the pathogenesis of Alzheimer's disease (Kelliher et al, 1999) while A increases ryanodine receptors expression and function in cortical neurons (Supnet et al, 2006). Taking into account importance of neuronal calcium mishandling in the development of Alzheimer's disease (Verkhratsky, et al, 1998), one can suggest involvement of cADPR-associated signaling pathways in observed ryanodine receptor dysfunction.…”
mentioning
confidence: 99%